Adlayer‐Free Large‐Area Single Crystal Graphene Grown on a Cu(111) Foil. Issue 35 (2nd July 2019) - Luo, Da; Wang, Meihui; Li, Yunqing; Kim, Changsik; Yu, Ka Man; Kim, Yohan; Han, Huijun; Biswal, Mandakini; Huang, Ming; Kwon, Youngwoo; Goo, Min; Camacho‐Mojica, Dulce C.; et al.
Abstract: To date, thousands of publications have reported chemical vapor deposition growth of "single layer" graphene, but none of them has described truly single layer graphene over large area because a fraction of the area has adlayers. It is found that the amount of subsurface carbon (leading to additional nuclei) in Cu foils directly correlates with the extent of adlayer growth. Annealing in hydrogen gas atmosphere depletes the subsurface carbon in the Cu foil. Adlayer‐free single crystal and polycrystalline single layer graphene films are grown on Cu(111) and polycrystalline Cu foils containing no subsurface carbon, respectively. This single crystal graphene contains parallel, centimeter‐long ≈100 nm wide "folds, " separated by 20 to 50 µm, while folds (and wrinkles) are distributed quasi‐randomly in the polycrystalline graphene film. High‐performance field‐effect transistors are readily fabricated in the large regions between adjacent parallel folds in the adlayer‐free single crystal graphene film. Abstract : Adlayer‐free large‐area single‐crystal graphene film is grown on Cu(111) foil by chemical vapor deposition. Such graphene film contains parallel long graphene folds up to centimeters in length, with a separation of ≈20–50 µm and a width of ≈80–100 nm, which allows straightforward fabrication of integrated high‐performance electronic devices within the regions between the folds.